If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 10 = 2(x + -9) + -1x Reorder the terms: 10 + X = 2(x + -9) + -1x Reorder the terms: 10 + X = 2(-9 + x) + -1x 10 + X = (-9 * 2 + x * 2) + -1x 10 + X = (-18 + 2x) + -1x Combine like terms: 2x + -1x = 1x 10 + X = -18 + 1x Solving 10 + X = -18 + 1x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + X = -18 + -10 + 1x Combine like terms: 10 + -10 = 0 0 + X = -18 + -10 + 1x X = -18 + -10 + 1x Combine like terms: -18 + -10 = -28 X = -28 + 1x Simplifying X = -28 + 1x
| 12+3y=4x | | 0.60x+0.40(100-x)=140 | | x(2x-7)=15 | | 2x+18=6y | | 2(x-3)=4(x-4) | | 14x^2+45x-14=0 | | 3x+42=5x-8 | | 196-4x=41x+21 | | 64x+8y=2 | | 11-8x=35-15x | | -65-10x=7x+20 | | 3(x+6)=2x-7+x | | 2x^2+2x=3 | | m+2=6m-3 | | X^2-4x=2x+7 | | 120=16t^2 | | 7x^2+21x=0 | | x^2+4x-10=0 | | 96-2x=25x+21 | | 7x^2+21=0 | | 4x-33=x | | 4(4-w)=2(15+4y) | | 9x-7x=173-35x | | 6x+63=10x-5 | | 9(4b-1)=2-(x+4) | | 3x+11=-61-9x | | 4x+5=2x^2-8 | | 120-3x=33x+24 | | 91-3x=12x+19 | | 2x^4=50x^2 | | 7-8x=37-22x | | (X+3)(x+3)=-10 |